The contents of plant pigments in bottom sediments of lakes Naroch, Myastro and Batorino - Smolskaya, Volha S.; Zhukava, Hanna A. (Journal of the Belarusian State University. Ecology, 2020)
The paper presents the results of the study of plant pigments in bottom sediments of the Narochanskie lakes (Naroch, Myastro and Batorino). Studies at the selected sites were aimed at identifying quantitative changes in plant pigments content in sediments at various depths. It has been shown that with increasing depth of the lakes there is an increase in the moisture content of bottom sediments and the content of organic matter in them, but there is a decrease in the density of sediments. A positive relationship was found between the content of total chlorophyll and carotenoids calculated on the unit of dry matter of bottom sediments and the depths of sample collection (r = 0.6 for Lake Naroch and r = 0.7 for Lake Myastro). All samples showed a high proportion of pheopigments in total chlorophyll (60–100 %). The content of total chlorophyll-a (without correction for the presence of pheopigments) was low: in Lake Naroch averaged (±SD) 16.5±18.2 μg/g in Lake Myastro – 6.4±6.2 μg/g and in Lake Batorino – 22.8±17.1 μg/g of dry mass of bottom sediments. The content of carotenoids was relatively low in the lakes Naroch and Myastro (on average 3.3±4.5 μg/g and3.6±4.1 μg/g of dry mass of bottom sediments, respectively), but in the Lake Batorino the content of this group of plant pigments was abnormally high – 35.8 ± 26.6 μg/g dry weight of bottom sediments.
Keywords: chlorophyll; pheopigments; carotenoids; bottom sediments; organic matter